Indikasi munculnya Kubah Lava berdasarkan Rekaman Seismik - Wittiri, S. R. (Indonesian Journal on Geoscience, 2009)
http://dx.doi.org/10.17014/ijog.vol4no2.20092In the last two decades, there are six volcanoes erupting and are ended up with the growth of lava dome at the crater. Among them, formerly there are three volcanoes that have crater lakes. For the intermediate magma, like most Indonesian volcanoes, the lava dome formation is a usual phenomenon. The interesting symptom is indicated by the seismic waves. They are supposed to relate to the magma breakthrough into the surface. The seismic phenomena of those volcanoes have a similarity, which can be estimated that theÂ  mechanism of rock fracturing is relatively similar. Â